208. Trends in Antibiotic Prescribing for Acute Respiratory Tract Infections and Implementation of a Provider-Directed Intervention Within the Veterans Affairs Healthcare System (VA). (26th November 2018) - Madaras-Kelly, Karl; Hruza, Hayli; Pontefract, Benjamin; Jones, Barbara; Jones, Makoto; Yao, Yiwen; Nevers, McKenna; Ying, Jian; Haaland, Ben; Kay, Chad; Christopher, Melissa; Samore, Matthew
Abstract: Background: We report VA-wide trends over time in acute respiratory infection (ARI) antibiotic prescribing, and early assessment of an intervention to improve ARI management. Methods: We created a retrospective cohort of ARI (sinusitis, pharyngitis, bronchitis, and URI-NOS) visits between 2009 and April 2018. Patients with complicating conditions were excluded. Antibiotic prescribing rates were calculated. A provider-directed VA-wide ARI campaign was initiated in October 2017. The Campaign was implemented locally by antibiotic stewards or regional personnel trained in academic detailing (AD). Campaign components: dashboards for tracking provider and facility prescribing metrics, printable feedback reports, and AD educational materials. Metrics include: ARI antibiotic prescribing rates, bronchitis/URI-NOS antibiotic prescribing rates, guideline-concordant antibiotic selection for sinusitis or pharyngitis, and proportion of ARI visits with a sinusitis diagnosis. A Logistic generalized estimating equation model assessed metrics over time pre-/postintervention and χ 2 tests compared guideline concordant antibiotic proportions pre-/postintervention. Results: There were 1, 580, 612 and 137, 421 ARI visits pre-/postintervention, respectively. Antibiotic prescribing decreased from 2009, annual odds ratio (OR) 0.94 [95% CI 0.93, 0.96; P < 0.001]. An additional effect was observed postintervention [OR 0.88, (0.84, 0.88), P < 0.001]. Bronchitis/URI-NOS prescribing rates decreased from 2009 [annual OR 0.94 (CI 0.93, 0.95), P < 0.001]. Additional effect was observed postintervention [OR 0.86, (0.81, 0.91), P < 0.001]. Overall, the proportion of ARI visits diagnosed with sinusitis increased [annual OR 1.09 (1.08, 1.10), P < 0.01], but the proportion of sinusitis diagnoses decreased [OR 0.72 (0.69, 0.75), P < 0.001] postintervention. Guideline-concordant antibiotic selection was 61.5% vs. 71.2% for sinusitis and 63.3% vs. 67.8% for pharyngitis pre-/postintervention, respectively (both P < 0.001). Conclusion: Antibiotic prescribing rates for ARIs within the VA have steadily declined since 2010. Additional decline in antibiotic prescribing was associated with the launch of a national campaign to improve ARI management. Disclosures: All authors: No reported disclosures.